Improving Riding Skills Understanding Using Directed Reading Thinking Activity Strategy (DRTA) Grade IV SD Inpres Bangkala II Kecamatan Manggala Kota Makassar - Abustang, Perawati Bte; Amaliyah, Nurhadifah; Fatimah, Waddi; Rahmat, Muh. (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
This research aimed at improving reading comprehension of grade IV students of SD Inpres Bangkala II on Bahasa Indonesia course using Directed Reading Thinking Activity (DRTA). This research applied qualitative approach type Classroom Action Research (CAR). The research was conducted in two cycles where each cycle consisted of three meetings. Every meeting was conducted through the research procedure started from planning, action, observation, and reflection. The subject ofthis research were 27 grade IV students of SD Inpres Bangkala II. The instruments used in this research were observation, evaluation test, field notes, and documentation and the data collection technique applied observation technique, test and documentation technique. Descriptive data analysis and qualitative data analysis were used. The result of the data showed that grade IV students' learning achievement of reading comprehension in SD Inpres Bangkala Il categorized as fair where minimum completeness criteria was 62,96% with 17 students passed. The students ' learning achievement improved in cycle Il where minimum completeness criteria was 92,59% categorized as very good with 25 students passed. It can he concluded that Directed Reading Thinking Activity (DRTA) strategv can improve grade IV students ' reading comprehension skill on Bahasa Indonesia course in SD Inpres Bangkala II